All Days 1998
DOI: 10.2118/40001-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Different Approach to Coupling a Reservoir Simulator with a Surface Facilities Model

Abstract: Hepguler, Barua, and Bard recently described the integration of a commercial reservoir simulator and a commercial production network simulator using the Parallel Virtual Machine interface. This paper outlines a somewhat different procedure, based on the same interface, that has been used to couple the same commercial black oil reservoir simulator ECLIPSE to a different surface model, namely the gas deliverability forecasting model FORGAS. For a given case, this new procedure yielded a significant reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Hepguler et al 17 and Tingas et al 18 presented timestep-level implicit couplings of (black-oil) reservoir and network simulators. Trick 19 …”
Section: Conventional Well Model a Basic Example Of Domain Decomposimentioning
confidence: 99%
“…Hepguler et al 17 and Tingas et al 18 presented timestep-level implicit couplings of (black-oil) reservoir and network simulators. Trick 19 …”
Section: Conventional Well Model a Basic Example Of Domain Decomposimentioning
confidence: 99%
“…8,9 It has since been extended and ported to the ECLIPSE compositional reservoir simulator. We shall summarize its current features here before describing in detail the coupling scheme that we employ.…”
Section: The Open Interfacementioning
confidence: 99%
“…Barroux et al (2000) suggested remedying the oscillations by replacing the well productivity with the derivative of rate against bottomhole pressure when producing IPR for coupling independent simulators at the Newton iteration level. Zapata et al (2001) investigated the use of an iteratively (reservoir-network) updated implicit bottomhole pressure to reduce the oscillations. The instability of a coupled system is also a cause of excessive computational time if separate models are solved iteratively (Coats et al 2004).…”
Section: Introductionmentioning
confidence: 99%